Legal Certainty in the Administration of Education: A National Legal Perspective - Ujang Cepi Barlian (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
Legal certainty is a fundamental principle in the administration of education, as it ensures clarity, consistency, and fairness in the implementation of educational policies and regulations. This article examines legal certainty in the administration of education from a national legal perspective, focusing on the regulatory framework governing educational institutions and the role of the state in guaranteeing the right to education. Using a normative juridical approach, this study analyzes statutory regulations, legal doctrines, and relevant legal principles related to educational governance. The findings indicate that legal certainty in education is essential to protect the rights and obligations of stakeholders, including learners, educators, educational institutions, and the government. However, challenges such as regulatory overlap, inconsistent policy implementation, and weak law enforcement may undermine legal certainty in educational administration. Therefore, strengthening legal harmonization, improving regulatory clarity, and enhancing institutional accountability are necessary to ensure the effective and lawful administration of education within the national legal system.